Performance-related pay and productivity - Claudio Lucifora; Federica Origo (IZA World of Labor, 2022)
A growing number of firms offer compensation packages that link pay to performance. The aim is to motivate workers to be more efficient while also increasing their attachment to the company, thereby reducing turnover and absenteeism. The effects of performance-related pay on productivity depend on the scheme type and design, with individual incentives showing the largest effect. Governments often offer tax breaks and financial incentives to promote performance-related pay, though their desirability has been questioned due to large deadweight losses involved. The diffusion of remote work will increase the relevance of performance-related pay.
Keywords: J31; J33; J52; L61; 330; performance-related pay; productivity; pay incentives; financial participation